The Concept, Fundamentals and Principles of Criminal Policy (Salam International Academic Journal, 2022)
Criminal Policy as a new science and knowledge in the form of legal studies has recently emerged, especially in communities like Afghanistan, where research and focus on new scientific findings have been less and poor for various reasons. The opportunity to study and do research in this field is scarce, so great deal of efforts should be made in this regard to open new scientific windows. Criminal Policy has gone through different periods to demonstrate its importance and position. Thus, countries are now concentrating on Criminal Policy to utilize its advantages so they establish social order. Criminal Policy is a broader format than Preventive and penal policies, which determines the main policy of a government in fight against violations, crimes, offenders and criminals. It recommends simple solutions for the ruling political body to move from the centralism of dealing with cases to the wider field of socialism of dealing with cases, and gives quasi-judicial institutions the opportunity to deal with lawsuits systematically and on the basis of justice. We should realize that without implementing criminal policy, it is impossible to decrease the level of crimes and criminals, and it is scientifically impossible to achieve a peaceful society. Thus, it is necessary to spread these concepts both in society through universities, schools, scientific media, social means, etc., and generalize the contents of the criminal policy in the system and government through the establishment and implementation of criminal laws and documents so that the expected results can be achieved from it. In this research, besides paying special attention to conceptual development of Criminal Policy, Afghanistan's criminal policy of the last hundred years has also been studied based on the available documents and evidence, and on the other hand, considering the country's cultural and environmental situation, special suggestions have been made for improvement of judicial system and the provision of justice services.
Keywords: criminal policy; crimes, punishments; violation; social reaction